The Amount of Phosphate Solubilization Depends on the Strain, C-Source, Organic Acids and Type of Phosphate. Issue 3 (16th March 2019) - Marra, Leandro Marciano; de Oliveira-Longatti, Silvia Maria; Soares, Cláudio Roberto Fonsêca Sousa; Olivares, Fábio Lopes; Moreira, Fatima Maria de Souza
Abstract: Although production of organic acids (OAs) is usually mentioned as the main mechanism of phosphate solubilization, the relationship between carbon sources (C-sources) and OAs produced during phosphate-solubilization by microorganisms is still poorly understood. We evaluated the influence of different C-sources on FePO4 ·2H2 O and Ca3 (PO4 )2 solubilization by bacteria and on the identity/quantity of the OAs produced. Our results showed that the amount of phosphate solubilization depends on the strain, C-source, OAs, and type of phosphate. Among the five strains under study isolated from cowpea nodules ( Rhizobium tropici strain UFLA 03-08, Acinetobacter sp. strain UFLA 03-09, Paenibacillus kribbensis strain UFLA 03-10, P. kribbensis strain UFLA 03-106, and Paenibacillus sp. strain UFLA 03-116), three of them solubilized Ca3 (PO4 )2 in all C-sources. The influence of C-sources on Ca3 (PO4 )2 -solubilization increased in the following order: cellulose < lactose < mannitol < glucose. A significant positive correlation between the amount of phosphorus solubilized from Ca3 (PO4 )2 and the concentration of total OAs in the presence of glucose and mannitol was observed for these three strains. In the presence of glucose, the highest solubilization rates are associated with high concentrations of tartaric acid, and in the presence of mannitol, are associated with maleic acid. Only one strain produced OAs in the medium with lactose and Ca3 (PO4 )2, but there was no OAs in the medium containing cellulose. Despite the production of OAs, albeit in small concentrations, in all the C-sources investigated, FePO4 ·2H2 O-solubilization was not observed. Thus, a relationship among C-sources, OAs, and phosphate solubilization was not always verified.